A Study of Biodegradable Geotextiles Used for Erosion Control. Issue 5 (1998) - Ogbobe, O.; Essien, K.S.; Adebayo, A.
Abstract : The physical properties of two geotextiles made of natural fibres, malvaceae and penduculata, are presented. The effectiveness of these biodegradable geotextiles in preventing soil erosion was studied and compared with a polypropylene fibre geosynthetic erosion control mat. A rainfall simulation apparatus was used on protected and unprotected slopes that were inclined at 10, 15, 20, 30, and 45° to the horizontal. The effective cover factor, defined as the ratio of soil loss from a protected slope to the soil loss from an unprotected slope, ranged from 0.24 to 0.49 for the penduculata geotextile and from 0.47 to 0.73 for the malvaceae geotextile. The effective cover factor ranged from 0.16 to 0.27 for the polypropylene erosion control mat.